OPTIMIZATION OF SURGICAL TACTICS FOR CALLETHISTERIES COMPLICATED BY MIRIZZI SYNDROME (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Mirizzi syndrome (SM) is one of the severe complications of cholelithiasis (GSD), resulting from acute or chronic fixation of gallstones in the neck of the gallbladder with impaired patency of the hepaticocholedochus and the formation of biliobiliary or biliodigestive fistulas. SM occurs in 0.2–5.7% of patients with cholelithiasis.